2020
DOI: 10.1091/mbc.e19-10-0586
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Tpm1.8 domains on actin filaments with single-molecule resolution

Abstract: Tropomyosins regulate dynamics and functions of the actin cytoskeleton by forming long chains along the two strands of actin filaments that act as gatekeepers for the binding of other actin-binding proteins. The fundamental molecular interactions underlying the binding of tropomyosin to actin are still poorly understood. Using microfluidics and fluorescence microscopy, we observed the binding of fluorescently labelled tropomyosin isoform Tpm1.8 to unlabelled actin filaments in real time. This approach in conju… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Whereas, in the absence of N-terminal acetylation, the T diss values of the HMW isoforms Tpm1.6 and Tpm2.1 exceeded those measured for the LMW isoforms Tpm3.1 and Tpm4.2 by 1 -6 C, the opposite was true for the isoforms with N-terminal acetylation. Compared with an increase of T diss by 10 -13 C upon acetylation of Tpm3.1 and Tpm4.2, acetylation of Tpm1.6 and Tpm2.1 leads to a reduction of T diss by 1 -2 C. In line with the kinetic binding model of Tpm molecules to actin (Bareja et al, 2020), the greater thermal stability of A-Tpm can be explained by stronger end-to-end contacts of Tpm molecules. Alternative explanations include stronger coordination of Tpm assembly on actin filaments or greater flexibility of Tpm cables.…”
Section: Impact Of N-terminal Tpm Acetylation On Actin-activated Atpa...supporting
confidence: 52%
“…Whereas, in the absence of N-terminal acetylation, the T diss values of the HMW isoforms Tpm1.6 and Tpm2.1 exceeded those measured for the LMW isoforms Tpm3.1 and Tpm4.2 by 1 -6 C, the opposite was true for the isoforms with N-terminal acetylation. Compared with an increase of T diss by 10 -13 C upon acetylation of Tpm3.1 and Tpm4.2, acetylation of Tpm1.6 and Tpm2.1 leads to a reduction of T diss by 1 -2 C. In line with the kinetic binding model of Tpm molecules to actin (Bareja et al, 2020), the greater thermal stability of A-Tpm can be explained by stronger end-to-end contacts of Tpm molecules. Alternative explanations include stronger coordination of Tpm assembly on actin filaments or greater flexibility of Tpm cables.…”
Section: Impact Of N-terminal Tpm Acetylation On Actin-activated Atpa...supporting
confidence: 52%
“…In addition, such direct observations further revealed information that seems inaccessible to other methods: that cofilin-induced severing occurred preferentially at the cluster boundary located toward the pointed end of the filament ( 31 , 44 , 45 ), how fast severing per cofilin cluster occurred ( 31 ), and how the action of cofilin is affected by other proteins ( 22 , 44 , 46 51 ) or by the oxidation of actin filaments ( 51 , 52 ). The cooperative formation of tropomyosin clusters was also confirmed on single filaments ( 48 , 49 , 53 ), and single-filament studies further revealed that tropomyosins independently decorate the two filament strands ( 48 , 54 ). Another example of key information provided by live single-filament observation is the assessment of formin processivity at the barbed end of a growing filament ( 32 , 55 , 56 ).…”
Section: Live Single-filament Studies Have Changed Our Ability To Understand Actin Dynamicsmentioning
confidence: 76%
“…Microfluidic devices and coverslips were prepared as described previously 61 . Images were collected on a custom built TIRF microscope described in Bereja et.…”
Section: Tirf Microscopy Data Acquisition and Analysismentioning
confidence: 99%
“…al. 61 with a power density of ∼1-3 W cm -2 (measured at the objective with the laser beam normal to the surface of the coverslip.…”
Section: Tirf Microscopy Data Acquisition and Analysismentioning
confidence: 99%